ปัจจัยเสี่ยงต่อหนอนพยาธิและติดเชื้อปรสิตลำไส้ในหมู่บ้านแห่งหนึ่งของจังหวัดเชียงราย - เรือนคำ วัชรพงษ์; นุ่นลอย สุเนตรา; พงค์จันตา อนุสรา; ก้อยชูสกุล พัชรา (Health Science, Science and Technology Reviews, 2015)
การวิจัยมุ่งหมายศึกษาปัจจัยเสี่ยงต่อหนอนพยาธิและติดเชื้อปรสิตลำไส้ในหมู่บ้านนางแลในของจังหวัดเชียงราย มีผู้เข้าร่วมการสำรวจ 171 คน ประกอบด้วยสามกลุ่มประชากรย่อยได้แก่ชาวไทยพื้นราบ/ชาวเขาเผ่าอาข่า/ชาวเขาเผ่าลาหู่ ปัจจัยเสี่ยงประกอบด้วยการบริโภคอาหารดิบแปรผันตั้งแต่ร้อยละ 13.3 ถึงร้อยละ 51.7 พฤติกรรมเสี่ยงพบมากที่สุดสองปัจจัยประกอบด้วย ดื่มน้ำไม่ต้มมากกว่าร้อยละ 90 และไม่สวมรองเท้าทำงานเกือบกึ่งหนึ่ง ดังนั้น การแทรกแซงด้วยการให้ความรู้จำเป็นสำหรับลดปัจจัยเสี่ยง Risk factors of helminths and intestinal protozoa infection in a village of Chiangrai province Watcharapong Ruankham*, Sunattra Nunloi, Anusara Pongjunta, Patchara Koychusakun Faculty of Health Science, Chiangrai Rajabhat University, Chiangrai Province 70000 The research aims to determine the risk factors for helminths and intestinal protozoa infection in Nanglae-Nai village, Chiangrai province. There were 171 persons from three subpopulations: Thai lowland, Akha, and Lahu hill tribe’s people, participating in the survey. The risk factors included consumption of raw food in the range of 13.3 to 51.7%, while the two common risk behaviors comprised of: unboiled water of 90%, and barefoot on working about nearly half. Thus the educational intervention is need for risk reduction.